Does Business Strategy hold the key to understanding Long-Run IPO Performance? - Weinberg, David Jeannot (2008)
We look at 135 Initial Public Offerings, across 14 different industries, made on the Official List (OL) and the Alternative Investment Market (AIM) of the London Stock Exchange (LSE) between 2004 & 2005. The purpose of this study was to look at the research undertaken on predicting post-flotation performance and introduce "Business Strategy" as a determinant variable. Using multiple regression analysis, we find that statistically, business strategy has only limited significance as an indicator of post-flotation success or failure, but find some evidence to suggest that "Revenue" and "Return on Assets" (ROA) as variables do find statistical significance in predicting short term performance. Furthermore we find that "Industry" also does not prove statistically significant in predicting post-flotation performance, but note that there are future opportunities to expand upon this initial research given greater resources and time.